A COMPREHENSIVE SYSTEMATIC REVIEW: EXPORT BARRIER IN INTERNATIONALIZATION OF AGRO-FOOD SMES - Razali, Siti Nor Diana; Yusof, Raja Nerina Raja; Mahomed, Anuar Shah Bali; Hamid, Mass Hareeza Ali (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The internationalisation of agro-food small and medium-sized enterprises (SMEs) is increasingly constrained by multifaceted export barriers that limit their competitiveness in emerging markets. Despite their vital role in sustaining economic growth and food security, agro-food SMEs often encounter institutional, managerial, and technological challenges that hinder their ability to expand abroad. This study systematically reviews the existing literature to identify and synthesise the key barriers shaping the export performance of agro-food SMEs. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, a rigorous search was conducted across two major databases, Scopus and EconBiz. The identification and screening process yielded 28 primary studies that met the inclusion criteria. Through thematic analysis of these studies, three overarching themes emerged: (1) institutional and environmental contexts shaping SME exporting, encompassing regulatory constraints, trade policies, and market volatility; (2) firm-level capabilities, finance, and managerial cognition, highlighting issues related to resource scarcity, limited managerial expertise, and financial barriers; and (3) networks, linkages, and digital/supply-chain technologies as enablers, emphasising the role of collaborative partnerships, innovation, and digitalisation in overcoming structural barriers. The findings underscore that export barriers are not isolated but interdependent, with institutional weaknesses amplifying firm-level limitations, while network and technological advancements serve as critical mitigating mechanisms. This review contributes to the understanding of export dynamics in agro-food SMEs by integrating insights across contexts and offering a framework that informs policymakers, practitioners, and scholars seeking to enhance SME internationalisation strategies.